Revitalized agriculture for balanced growth and resilient livelihoods: Toward a rural development strategy for Mon State - Filipski, Mateusz J.; Nischan, Ulrike; van Asselt, Joanna; Belton, Ben; Kennedy, Adam; Hein, Aung; Dorosh, Paul A.; Boughton, Duncan (International Food Policy Research Institute, 2017)
This report offers specific policy and investment options articulated around two broad areas: (1) stimulating growth in agriculture and sustainable management of fisheries and (2) providing public infrastructure and services that strengthen the enabling environment. A plan to stimulate growth in agriculture and fisheries, the first broad area, could be centered around the following set of goals: revitalize the rubber sector, develop high-value fresh products, improve rice productivity, modernize land and input markets, expand access to loans for machinery and seasonal input purchases, strengthen agricultural extension services to ensure dynamism in Mon State’s farm sector, improve management of marine capture fisheries, and facilitate expansion of aquaculture. The first part of the report details the challenges and potential solutions presented by each of these points. The second part of the report details options to create a growth-enabling environment through public infrastructure and services, centered around the following goals: improve the budgetary and fiscal process to enable locally driven public investment, improve access to and reliability of infrastructure, expand the formal credit market, promote productive investment by the private sector, strengthen regulatory frameworks for the construction sector, exploit the potential for the development of tourism, and improve the quality of and access to education and health services.